The significance of karyotyping and azoospermia factor analysis in patients with nonobstructive azoospermia or oligozoospermia - Shin-Wen Chen; Chih-Ping Chen; Schu-Rern Chern; Yu-Ling Kuo; Chien-Ling Chiu (Elsevier, 2022)
Objective: We present our study about the significance of karyotyping and azoospermia factor(AZF) analysis in patients with azoospermia or oligozoospermia. Materials and methods: We retrospectively reviewed 141 Taiwanese patients with nonobstructive azoospermia and 45 Taiwanese patients with oligozoospermia at MacKay Memorial Hospital, Taiwan, from 2010 to 2021 to determine the significance of karyotyping and azoospermia factor analysis. The karyotyping was analyzed using the Giemsa banding method. The AZF microdeletions were determined using multiplex polymerase chain reaction using primers specifically flanking the AZF subregions. Results: We found that 7.80% of patients with nonobstructive azoospermia had AZF microdeletions and 19.86% of patients with nonobstructive azoospermia had chromosomal anomalies or polymorphic variations. Furthermore, 4.44% of patients with oligozoospermia had AZF microdeletions, and 4.44% of patients with oligozoospermia had chromosomal anomalies or polymorphic variations. Conclusion: In this study, 25.53% of patients with nonobstructive azoospermia and 8.88% of patients with oligozoospermia had abnormal findings. The significance of karyotyping and azoospermia factor analysis is more critical in patients with nonobstructive azoospermia than patients with oligozoospermia. Both karyotyping and AZF analysis could prevent delayed treatment for male infertility through accurate diagnosis and appropriate treatment. The number of our patients with AZFc microdeletion was also higher than that of patients with AZFa or AZFb. The spermatogenic potential may gradually decline in patients with AZFc microdeletion. The earlier is the diagnosis, the earlier will be the retrieval of testicular spermatozoa.